2021
DOI: 10.3390/ijerph18115988
|View full text |Cite
|
Sign up to set email alerts
|

African Herbal Medicines: Adverse Effects and Cytotoxic Potentials with Different Therapeutic Applications

Abstract: The African continent is naturally endowed with various plant species with nutritional and medicinal benefits. About 80% of the people in developing countries rely on folk medicines to treat different diseases because of indigenous knowledge, availability, and cost-effectiveness. Extensive research studies have been conducted on the medicinal uses of African plants, however, the therapeutic potentials of some of these plants has remained unexploited. Over the years, several studies have revealed that some of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(46 citation statements)
references
References 163 publications
(118 reference statements)
0
45
1
Order By: Relevance
“…THs of the study area know the effect of overdose use of some TMPs on the health of patients. This study result is different from the report of most communities of Africa [ 58 ] that indicates no regulated use and adverse effect [ 59 ]. They provide differential usage information and prescription to their patients and determine the dosage supporting different conditions, status of patients, and nature of the ailment with precautions.…”
Section: Discussioncontrasting
confidence: 99%
“…THs of the study area know the effect of overdose use of some TMPs on the health of patients. This study result is different from the report of most communities of Africa [ 58 ] that indicates no regulated use and adverse effect [ 59 ]. They provide differential usage information and prescription to their patients and determine the dosage supporting different conditions, status of patients, and nature of the ailment with precautions.…”
Section: Discussioncontrasting
confidence: 99%
“…These phytochemicals possess different pharmacological potentials; however, they could be toxic at a high concentration [132]. The toxicology study of several plants with significant therapeutic potentials has been reported in the literature [133]. Likewise, some researchers have investigated the toxicity of the solvent extracts of C. volubile to ascertain its safety.…”
Section: Safety Concerns Regarding the Use Of The Plant (Toxicity Studies)mentioning
confidence: 99%
“…Another key concern is that the increased use of herbal medicines has been accompanied by their adulteration, which includes increased use of synthetic compounds to increase profit levels; however, this leads to concerns with quality control unless proactively addressed ( Ekar and Kreft, 2019 ; Enioutina et al, 2020 ; Kum et al, 2021 ; Okaiyeto and Oguntibeju, 2021 ). Alongside this, there have also been an increase in the extent of falsified medicines, including herbal medicines, for both life style and health-related conditions across countries ( BottomLineInc, 2014 ; Newsmax_Fake_2015 ; Nuryunarsih, 2016 ; Ekar and Kreft, 2019 ).…”
Section: Introductionmentioning
confidence: 99%